HTML 5 (HyperText Markup Language) - Lavanya, R. (Ane Books, 2014)
HyperText Markup Language (HTML) is specially designed keeping in mind the ever-growing needs of undergraduate and postgraduate students. It also provides a wealth information and serves as an encyclopedia to those who aspire to create their own websites.